2017
DOI: 10.5935/1518-0557.20170061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sperm DNA fragmentation on embryo development: clinical and biological aspects

Abstract: ObjectiveThe aim of this study was to investigate the effect of sperm DNA fragmentation on fertilization rate, embryo development (blastulation rate), and pregnancy outcomes for ICSI cycles performed in a cohort of couples using donor eggs and to assess the remaining embryos that were not transferred or frozen for apoptotic markers.MethodsEighty-two women (egg recipients) were included in the study (2016) were included in the study. The recipients' mean age was 41.8±5.1 y/o (36-49), while the egg donors' mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 37 publications
9
57
0
Order By: Relevance
“…Third, 284 meeting abstracts, 86 reviews or guidelines, seven letters or comments, four duplicate report studies and 50 studies for which data could not be extracted were excluded. Fourth, seven studies scoring 5 on the modified Newcastle–Ottawa scale were excluded because of its inclusion of unrepresentative participants and not control baseline factors (Aguilera Duvisón et al, ; Check, Graziano, Cohen, Krotec, & Check, ; Esteves, Sanchez‐Martin, Sanchez‐Martin, Schneider, & Gosalvez, ; Henkel et al, ; Ozmen et al, ; Alvarez Sedo et al, ; Tandara et al, ) In addition, six articles (Cebesoy, Ünlü, Aydos, & Baltaci, ; Dar et al, ; Jiang, He, Wang, & Zhu, ; Wang et al, ; Zhang et al, ; Zini et al, ) measuring DNA fragmentation by the acridine orange test were excluded. Six articles (Belloc et al, ; Cebesoy et al, ; Duran, Morshedi, Taylor, & Oehninger, ; Hu, Zhu, Liu, & Fan, ; Muriel et al, ; Ren, Sun, Ku, Chen, & Wu, ; Yang et al, ) in which couples received intrauterine insemination (IUI) were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, 284 meeting abstracts, 86 reviews or guidelines, seven letters or comments, four duplicate report studies and 50 studies for which data could not be extracted were excluded. Fourth, seven studies scoring 5 on the modified Newcastle–Ottawa scale were excluded because of its inclusion of unrepresentative participants and not control baseline factors (Aguilera Duvisón et al, ; Check, Graziano, Cohen, Krotec, & Check, ; Esteves, Sanchez‐Martin, Sanchez‐Martin, Schneider, & Gosalvez, ; Henkel et al, ; Ozmen et al, ; Alvarez Sedo et al, ; Tandara et al, ) In addition, six articles (Cebesoy, Ünlü, Aydos, & Baltaci, ; Dar et al, ; Jiang, He, Wang, & Zhu, ; Wang et al, ; Zhang et al, ; Zini et al, ) measuring DNA fragmentation by the acridine orange test were excluded. Six articles (Belloc et al, ; Cebesoy et al, ; Duran, Morshedi, Taylor, & Oehninger, ; Hu, Zhu, Liu, & Fan, ; Muriel et al, ; Ren, Sun, Ku, Chen, & Wu, ; Yang et al, ) in which couples received intrauterine insemination (IUI) were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies generally scored well on the modified Newcastle–Ottawa quality assessment scale: six studies scored 9, 11 studies scored 8, seven studies scored 7, and five studies scored 6 (Table ). Seven studies which did not control the baseline factors (like age, BMI and FSH) or female factors received a score of 5 and were excluded (Aguilera Duvisón et al, ; Check et al, ; Esteves et al, ; Henkel et al, ; Ozmen et al, ; Alvarez Sedo et al, ; Tandara et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, sperm selection on the basis of viability and morphology does not eliminate the chance of DNA‐damaged spermatozoa being inseminated because of the potential of spermatozoa with apparently normal morphology having DNA fragmentation . Although sperm with slightly damaged DNA can still achieve fertilization, sperm with the “invisible damaged” DNA, once mistakenly selected to fertilize oocytes, could result in fertilization failure, impaired normal embryo development, and even miscarriage . Other promising techniques such as microfluidic platform that aims to provide single‐cell level investigation and selection of high‐quality sperm cell, optical tweezers that has been used for measuring physiological properties of sperm cells such as swimming speed, and swimming forces to select the most energetic sperm cells, however, lack biochemical features regarding DNA integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Simon et al reported a low fertilization rate in patients with high levels of SDF using Comet assay [51]. Several studies have reported a negative correlation between SDF and fertilization rates, pregnancy, and embryo quality [52][53][54]. Barehet al reported high incidence of SDF in normozoospermic male partners of couples with recurrent pregnancy loss (RPL) [55].…”
Section: Discussionmentioning
confidence: 99%